Expanding the materials space of DNA via organic-phase ring-opening metathesis polymerization - Tan, Xuyu (Chem, 2019)
Herein, we develop a facile route to bring DNA to the organic phase, which greatly expands the types of structures accessible using DNA macromonomers. Phosphotriester- and exocyclic amine-protected DNA was synthesized and further modified with a norbornene moiety, which enables homopolymerization via ring-opening metathesis to produce brush-type DNA graft polymers in high yields. Subsequent deprotection cleanly reveals the natural phosphodiester DNA. The method not only achieves high molecular weight DNA graft polymers but when carried out at low monomer:catalyst ratios, yields oligomers that can be further fractionated to molecularly pure, monodisperse entities with one through ten DNA strands per molecule. In addition, we demonstrate substantial simplification in the preparation of traditionally difficult DNA-containing structures, such as DNA/poly(ethylene glycol) diblock graft copolymers and DNA amphiphiles. We envision that the marriage of oligonucleotides with the vast range of organic-phase polymerizations will result in many new classes of materials with yet unknown properties.